Lifestyle Behaviours of Children and Adolescents During the First Two Waves of the COVID-19 Pandemic in Switzerland and Their Relation to Well-Being: An Observational Study - Gabriela P. Peralta; Anne-Linda Camerini; Sarah R. Haile; Christian R. Kahlert; Christian R. Kahlert; Elsa Lorthe; Laura Marciano; Laura Marciano; Andres Nussbaumer; Thomas Radtke; Agne Ulyte; Milo A. Puhan; et al. (Frontiers Media S.A., 2022)
Objectives: To describe changes in adherence to recommendations for physical activity (PA), screen time (ST), and sleep duration over the first two waves of the pandemic in Switzerland, and to assess the associations of these lifestyle behaviours with life satisfaction and overall health as well-being indicators.Methods: In this observational study, we included 2,534 participants (5-16 years) from four Swiss cantons. Participants, or their parents, completed repeated questionnaires and reported on their (child's) lifestyle and well-being, between June 2020 and April 2021. We used linear and logistic regression models to assess the associations between lifestyle and well-being.Results: The percentage of children meeting the recommendations for PA and ST decreased from the pre-pandemic period to the first wave, with a slight recovery during the second wave. Participants meeting all three recommendations during the second wave were more likely to report excellent health (OR: 1.65 [95% CI: 1.00-2.76]) and higher life satisfaction (β: 0.46 [0.16-0.77]) in early 2021 than participants not meeting any recommendation.Conclusion: We showed a substantial impact of the COVID-19 pandemic on children's and adolescents' lifestyle, and a positive association between meeting lifestyle recommendations and well-being.